EFFECT OF THE PROPORTION OF SORGHUM FLOUR : WHEAT AND CARRAGEENAN ON THE QUALITY OF PATIN FISH BURGER - Dwiki Febrian, Nurdin; -, Jariyah; Winarti, Sri (Food Science and Technology Journal (Foodscitech), 2022)
Patty Burger is minced meat (usually beef, but sometimes other meats), shaped round, flattened, steamed first, and then fried in butter or grilled over coals. Catfish meat was chosen because it is high in protein and low in fat, the use of proportions of sorghum flour and wheat flour to improve product quality so that it is not easily crushed, the addition of carrageenan as a stabilizer to improve texture. This study aims to determine the effect of the proportion of sorghum flour and wheat flour with the addition of carrageenan on the quality of the catfish burger patty. This study used a factorial Completely Randomized Design (CRD) with two factors, namely factor I the proportions of sorghum flour and wheat flour (60%:40%, 70%:30%, 80%:20%) and factor II carrageenan concentration (0, 5%, 1%, 1.5%). The data obtained were analyzed using ANOVA, if there was a significant difference between treatments, a 5% DMRT further test was carried out. This study showed a significant interaction between the proportions of sorghum flour and wheat flour with the observation parameters of moisture content, ash content, fat content, WHC, Penetrometer texture, starch content, food fiber, r, and hedonic organoleptic tests, aroma scores, color scores, taste scores. The best results were obtained in the A2B2 treatment, namely the proportion of sorghum and wheat flour (70%:30%) with the addition of 1.0% carrageenan with the characteristics of water content 57.74%, protein content 14.47%, fat content 5.18%, Texture 0.13 mm/gr/sec, WHC 16.50%, Starch 17.43% and a score of 3.87 (Like) for Color 3.87, 3.82 (Slightly Likes) for Taste and 3.75 (Slightly Likes) for scent Keywords: burger patty, sorghum flour, wheat flour, carrageenan